Age at Marriage and Fertility Pattern of Adolescent Married Women in Rural Bangladesh - Ahmed, Shaila; Nahar, Shamsun; Amin, Md Nurul; Shirin, Sonia (Ibrahim Medical College Journal, 2009)
This cross sectional descriptive study was conducted in two purposively selected rural areas of Faridpur district - Alfadanga and Boalmari. The objectives were to find out the age at marriage and fertility pattern amongst the adolescent married women residing in the study areas. A total of 426 women were selected purposively and interviewed using a pre-tested structured questionnaire. Most (97.2%) were in the age group of 15-19 years, being married by 15.5 ± 1.5 years. Although 57.5% had a secondary level education, almost all (97%) were found to be housewives. Monthly income was between Taka 2001-4000 in 41.3% of the households. Regarding fertility pattern, 19% of the adolescent women were found to be pregnant at the time of survey. The total fertility rate (TFR) among this age group was estimated to be 2.6 per woman. To help improve the situation, awareness on the negative consequences of early marriage and consequent childbearing needs to be created not only among the young adolescent girls but should be targeted towards their parents too. Ibrahim Med. Coll. J. 2007; 1(2): 9-12 Key Words: Adolescence, early marriage, rural women, fertility pattern, developing countries. doi: 10.3329/imcj.v1i2.2898